2019
DOI: 10.3390/math7100898
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Bitcoin Price Prediction Using Deep Learning

Abstract: Bitcoin has recently received a lot of attention from the media and the public due to its recent price surge and crash. Correspondingly, many researchers have investigated various factors that affect the Bitcoin price and the patterns behind its fluctuations, in particular, using various machine learning methods. In this paper, we study and compare various state-of-the-art deep learning methods such as a deep neural network (DNN), a long short-term memory (LSTM) model, a convolutional neural network, a deep re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 21 publications
(30 reference statements)
1
76
0
Order By: Relevance
“…Simple linear time series models sometimes leave certain aspects of economic and financial data unexplained [29]. That is why some authors tested nonlinear time series models to model nonlinear behavior in economic and financial time series data [13], [14], [16], [20]- [28]. Table 2 shows a summary for the research on price prediction of cryptocurrencies comparing the used AI techniques and datasets in each paper.…”
Section: A Price Prediction/forecastingmentioning
confidence: 99%
See 3 more Smart Citations
“…Simple linear time series models sometimes leave certain aspects of economic and financial data unexplained [29]. That is why some authors tested nonlinear time series models to model nonlinear behavior in economic and financial time series data [13], [14], [16], [20]- [28]. Table 2 shows a summary for the research on price prediction of cryptocurrencies comparing the used AI techniques and datasets in each paper.…”
Section: A Price Prediction/forecastingmentioning
confidence: 99%
“…Mean square error (MSE), root mean square error (RMSE) and mean absolute error (MAE) were used in [21], [25]. Mean absolute percentage error (MAPE) was used in [20], [22], [26]. Accuracy, recall, precision and F1 Score were used in [16], [20], [27].…”
Section: A Price Prediction/forecastingmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum achieved accuracy was equal to 94.5% and 99.3% for 100 and 1000 first system calls, respectively, with a simple CNN configuration [14]. In recent years, research on the combination of CNNs and RNNs into one model has shown promising results [72][73][74] and was applied from image recognition to Bitcoin price prediction tasks. This encouraged many researchers to apply similar methods in the IDS research field.…”
mentioning
confidence: 99%